INTEGRASI 7 POE ATIKAN HARI AJEG NUSANTARA DALAM PEMBELAJARAN MEMBACA TEKS NARASI DI SEKOLAH DASAR - Alvin Muhammad Fauzi; Cantika Sri Agustin; Khosyi Anindya Chotimah; Nadia Haeriska; Indah Nurmahanani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by reading instruction in elementary schools that still focuses on cognitive aspects and has not optimally integrated character values, particularly nationalism and love for local culture. This study aimed to describe and analyze the integration of Ajeg Nusantara values in the 7 Poe Atikan program within narrative text reading instruction in elementary schools. The study employed a qualitative approach with a descriptive analytical method. The research subject was a fourth-grade elementary school teacher, while data were collected through in-depth interviews. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the integration of Ajeg Nusantara values was carried out through habituation activities, the selection of narrative texts themed around Nusantara culture, and the connection of learning materials with students’ real-life experiences. The integration was able to develop students’ moral knowing, moral feeling, and moral action. In addition to improving literacy skills, the learning process also fostered pride in local culture, tolerance, discipline, and created a more active classroom atmosphere that respected diversity.